Clinical efficacy and safety of aidi injection combination with vinorelbine and cisplatin for advanced non–small-cell lung carcinoma: A systematic review and meta-analysis of 54 randomized controlled trials. (March 2020) - Xiao, Zheng; Jiang, Yuan; Wang, Cheng-Qiong; Hu, Shan-Shan; Huang, Xiao-Rong; Chen, Xiao-Fan; Huang, Jun; Shan, Li-Jing; Tang, Yu-Hong; Wang, Yu-He; Gong, Qi-Hai; Feng, Ji-Hong; et al.
Graphical abstract: Highlights: Meta-analysis involving 54 trials containing 4, 053 patients. Aidi injection improved tumor response, and reduced ARDs. Aidi injection may show a synergistic effect for NP regimen, reduce the dosage of cisplatin. Aidi injection may lower the threshold for NP use. Treatment with 50 mL/day, 2 weeks/cycle for two to three cycles may be optimal usage. Abstract: The Aidi injection contains multiple active ingredients, including astragaloside (Re, Rb1, and Rg1), ginsenoside, cantharidin, elentheroside E, and syringin, and it is administered with vinorelbine and cisplatin (NP) to treat non–small-cell lung carcinoma (NSCLC). In this study, we performed a systematic review and meta-analysis to determine the clinical efficacy and safety of the Aidi injection with NP, and the optimal threshold and treatment regimen to produce the desired responses. We collected all studies regarding the Aidi injection with NP for NSCLC from Chinese and English databases (up to April 2019). Risk of methodological bias was evaluated for each study. Data for analysis were extracted using a standard data extraction form. Evidence quality was assessed following the Grading of Recommendations Assessment, Development and Evaluation approach. We included 54 trials containing 4, 053 patients for analysis. Combining the Aidi injection with NP significantly increased the objective response rate (odds ratio [OR], 1.32; confidence interval [CI], 1.23, 1.42), disease control rate (OR, 1.14; CI, 1.11, 1.18), and quality of life (OR, 1.80; CI, 1.61, 1.98), with decreased risks of myelosuppression, neutropenia, thrombocytopenia, anemia, gastrointestinal reaction, and liver dysfunction. For patients with a Karnofsky Performance Status score of ≥60, the Aidi injection (50 mL/day, two weeks/cycle, with two to three cycles) treatment with vinorelbine (25 mg/m 2 ) and cisplatin (30–35 mg/m 2 or 40–50 mg/m 2 ) might be the optimal regimen for producing the desired tumor response and achieving a good safety level. Most results were robust, and their quality was moderate. The results suggest that administration of the Aidi injection and concomitant NP is beneficial to NSCLC, and provide evidence for the optimal threshold and treatment regimen that may improve tumor response with a good safety level.